Private equity challenge: project Tundra - valuation - Eickhoff, Felix (2023)
Project Tundra investigates the LBO of Husqvarna Group, a renowned manufacturer of outdoor equipment and construction tools. The company is positioned to benefit from high growth as a result of its fundamental focus on robotics and autonomous solutions. The LBO encompasses a strategic shift from the phase-out of petrol products, in combination with changing market dynamics, to meet a new customer demand related to sustainability and environmentally friendly solutions. The projections in this report suggest the LBO of Husqvarna to yield a Multiple on Invested Capital of 3.1x and an IRR of 25.1% over a five-year holding period.